Asian and Trans‐Pacific Dust: A Multimodel and Multiremote Sensing Observation Analysis. Issue 23 (6th December 2019) - Kim, Dongchul; Chin, Mian; Yu, Hongbin; Pan, Xiaohua; Bian, Huisheng; Tan, Qian; Kahn, Ralph A.; Tsigaridis, Kostas; Bauer, Susanne E.; Takemura, Toshihiko; Pozzoli, Luca; Bellouin, Nicolas; et al.
Abstract: Dust is one of the dominant aerosol types over Asia and the North Pacific Ocean, but quantitative estimation of dust distribution and its contribution to the total regional aerosol load from observations is challenging due to the presence of significant anthropogenic and natural aerosols and the frequent influence of clouds over the region. This study presents the dust aerosol distributions over Asia and the North Pacific using simulations from five global models that participated in the AeroCom phase II model experiments, and from multiple satellite remote sensing and ground‐based measurements of total aerosol optical depth and dust optical depth. We examine various aspects of aerosol and dust presence in our study domain: (1) the horizontal distribution, (2) the longitudinal gradient during trans‐Pacific transport, (3) seasonal variations, (4) vertical profiles, and (5) model‐simulated dust life cycles. This study reveals that dust optical depth model diversity is driven mostly by diversity in the dust source strength, followed by residence time and mass extinction efficiency. Key Points: Dust and total aerosol over Asia and the North Pacific Ocean are evaluated using observations and models Satellites estimate a 35–70% decrease of DOD from the west Pacific to the east Pacific DOD model diversity is driven mostly by diversity in the dust source strength, followed by residence time and mass extinction efficiency